1976
DOI: 10.3758/bf03213230
|View full text |Cite
|
Sign up to set email alerts
|

Semantic priming and retrieval from lexical memory: Evidence for facilitatory and inhibitory processes

Abstract: Immediately prior to each visually presented target letter string to which the subject made a speeded word-nonword classification response, a visually presented prime to which no overt response was required was shown for 360, 600, or 2,000 msee. For word (W) target trials, the priming event was either a semantically neutral warning signal (Condition NX), a word semantically related to the target word (Condition R), or a word semantically unrelated to the target word (Condition U); for nonword (N) target trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
385
7
3

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(417 citation statements)
references
References 5 publications
22
385
7
3
Order By: Relevance
“…Thus, the effects of repetition priming studied in the laboratory, particularly with tasks that require the production of target stimuli, are usually short lived and do not last longer than few hours (e.g., Graf & Mandler, 1984;Squire, Shimamura, & Graf, 1985) or few days (e.g., Sloman, Hayman, Ohta, Law, & Tulving, 1988;Tulving, Schacter, & Stark, 1982; but see Tulving, Hayman, & Macdonald, 1991). 9 As to the effects of semantic priming, they can be dramatically reduced or even Specifically, when the spreading of activation in a semantic network is studied in laboratory, the prime/target pairs that are used are almost always the abstract names of categories and category exemplars (e.g., Bird-Robin) or names of associatively related concepts (e.g., Doctor-Nurse) (see e.g., Neely, 1976). Our results show that this type of activation does occur in the course of everyday life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effects of repetition priming studied in the laboratory, particularly with tasks that require the production of target stimuli, are usually short lived and do not last longer than few hours (e.g., Graf & Mandler, 1984;Squire, Shimamura, & Graf, 1985) or few days (e.g., Sloman, Hayman, Ohta, Law, & Tulving, 1988;Tulving, Schacter, & Stark, 1982; but see Tulving, Hayman, & Macdonald, 1991). 9 As to the effects of semantic priming, they can be dramatically reduced or even Specifically, when the spreading of activation in a semantic network is studied in laboratory, the prime/target pairs that are used are almost always the abstract names of categories and category exemplars (e.g., Bird-Robin) or names of associatively related concepts (e.g., Doctor-Nurse) (see e.g., Neely, 1976). Our results show that this type of activation does occur in the course of everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in semantic priming experiments such indirect activations have been assessed by measuring reaction times (in a lexical decision task) to target words which are semantically related to previously presented primes (e.g., Fischler, 1977;Neely, 1976;. In addition, there are several other lines of research which have shown that automatic activation of related information in response to a target word can exert strong effects on performance in such different tasks as free recall and recognition (Mandler, & Rabinowitz, 1981;Roediger, & McDermott, 1995), cued recall (Nelson et al, 1998), implicit memory tasks (McDermott, 1997), reading and text comprehension (Kintsch, 1988;Sharkey, & Mitchell, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Words are represented as networks of interconnected nodes, with either a one-to-one representation of a word and a node or a distributed representation of various word features and selected sets of nodes. Presentation of a word activates its lexical representation, with activation spreading automatically or obligatorily to other related lexical entries (Collins and Loftus, 1975;Neely, 1976). Various word features, such as orthographic, phonological and semantic are represented in the lexicon, but the most powerful determinant of processing are semantic representations of concepts of corresponding words, which is the heart of language (Fischler, 1997).…”
Section: Attention and Semantic Processesmentioning
confidence: 99%
“…The neutral primes consisted of a row of uppercase Xs (e.g., XXXX-eggs) and were used to determine whether the effects of the three other prime types should be attributed to costs or benefits (Neely, 1976;Posner & Snyder, 1975). The number of Xs in the neutral primes was either four or five, depending on the number of letters in the target.…”
Section: Parafoveal Priming 459mentioning
confidence: 99%